2023
DOI: 10.1007/s11032-023-01382-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin, variation, and selection of natural alleles controlling flowering and adaptation in wild and cultivated soybean

Abstract: Soybean (Glycine max) is an economically important crop worldwide, serving as a major source of oil and protein for human consumption and animal feed. Cultivated soybean was domesticated from wild soybean (Glycine soja) which both species are highly sensitive to photoperiod and can grow over a wide geographical range. The extensive ecological adaptation of wild and cultivated soybean has been facilitated by a series of genes represented as quantitative trait loci (QTLs) that control photoperiodic flowering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Flowering is one of the most important traits to describe how soybean varieties adapt to the ecological environment [17]. Multiple quantitative trait loci (QTLs) and genes have been identified that regulate the photoperiod pathways and influence the time to flowering [18][19][20][21], but only a few that reveal how the time to flowering is affected by temperature have been reported, especially the active accumulated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Flowering is one of the most important traits to describe how soybean varieties adapt to the ecological environment [17]. Multiple quantitative trait loci (QTLs) and genes have been identified that regulate the photoperiod pathways and influence the time to flowering [18][19][20][21], but only a few that reveal how the time to flowering is affected by temperature have been reported, especially the active accumulated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Some new varieties also show improved quality characteristics such as higher protein and fat content in the seeds. This allows farmers to grow soybean in a wide range of regions, thereby promoting diversity of production and increasing its sustainability [18]. Years of trials and progeny evaluation help select the best soybean varieties with high yields and desirable traits.…”
Section: Discussionmentioning
confidence: 99%
“…The broad geographic distribution and resilience to harsh environmental conditions suggest a wealth of adaptive genes within G. soja [ 9 , 11 ]. Numerous beneficial genes or genetic loci have been identified in G. soja resources, including those conferring abiotic resistance [ 18 , 19 , 20 , 21 ], biotic resistance [ 22 ], and adaptation to various environmental conditions [ 9 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that the introgression from adapted sympatric wild soybeans facilitated the local adaptation of landraces during the expansion of cultivated soybean [ 17 ]. Numerous beneficial genes or genetic loci have been identified from G. soja resources, including those conferring abiotic resistance [ 18 , 19 , 20 , 21 ], biotic resistance [ 22 ], and adaptation to various environmental conditions [ 23 , 24 , 25 , 26 ]. Consequently, wild soybean represents a valuable gene reservoir for the genetic enhancement of cultivated soybeans, providing them with the capacity to adapt to new environments.…”
Section: Introductionmentioning
confidence: 99%